ANALYSIS OF DYNAMICS OF ASSETS OF THE BANKING SECTOR OF THE RUSSIAN FEDERATION AND IT’S INFLUENCE ON EFFICIENCY OF CONTACT SUPERVISION OF THE CENTRAL BANK OF RUSSIA - F. Shogenova (Вестник университета)
The article analyzes the dynamics of assets of the banking sector of the Russian Federation and further impact on the efficiency of contact supervision of the Bank of Russia. Provides information about the change of the number of credit institutions number of operating credit institutions in Russia, the main indicators of the banking sector of the Russian Federation, data on the structure and dynamics of assets of credit institutions. The author provides an analysis on changes of the main indicators of the banking sector.